Lithium supplement additive and preparation method and application thereof
By controlling the density and structure of lithium supplement additives and ensuring their reasonable distribution in the electrodes, the deformation problem caused by the unreasonable particle density of lithium supplement materials for the positive electrode of lithium supplement materials of lithium ion batteries is solved, and the coulomb efficiency and cycling performance of the battery are improved.
Patent Information
- Application Number
- CN202111669646.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-30
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-12-30
AI Technical Summary
The existing lithium-ion battery positive electrode lithium supplement material has unreasonable particle density distribution, which leads to deformation or rupture of active substance particles, affecting the Coulomb efficiency and cycling performance of the electrode.
Provide a lithium supplement additive, whose loose bulk density and tap density are within a specific range, have a core-shell structure and a hydrophobic encapsulation layer, by controlling the particle morphology and molecular formula as aLiFeO2·bLi2O·cMxOy, doped elements such as Ni, Co , Mn, Ti, Al, Cu, V, Zr, ensure reasonable distribution and stability in the electrode.
Effectively fill and scatter between the particles of the electrode active material, reduce stress, prevent deformation and rupture, improve the electrode capacity and circulation performance, and improve the first-time Coulomb efficiency and circulation performance of lithium-ion batteries.
Smart Images

Figure CN115312767B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of lithium-ion batteries, and specifically relates to a lithium supplement additive and a preparation method and application thereof. Background Art
[0002] The oil energy crisis in the 1960s and 1970s forced people to look for new alternative energy sources. Lithium-ion batteries are considered to be one of the most promising energy sources because of their high operating voltage and energy density, relatively small self-discharge level, no memory effect, no heavy metal pollution such as lead and cadmium, and ultra-long cycle life.
[0003] During the first charging process of lithium-ion batteries, the negative electrode surface is usually accompanied by the formation of a solid electrolyte membrane SEI film, which consumes a large amount of Li + , which means that Li released from the positive electrode material + Part of it is irreversibly consumed, and the reversible specific capacity of the corresponding battery cell is reduced. The negative electrode material, especially the silicon-based negative electrode material, will further consume Li + , resulting in the first time low Coulomb efficiency.
[0004] In order to improve the low coulombic efficiency problem caused by irreversible loss of the negative electrode, in addition to pre-lithiation of the negative electrode material and the pole piece, lithium supplementation of the positive electrode can also achieve the requirements of high energy density. The theoretical capacity of lithium-rich iron-based materials is as high as 867mAh / g, the operating voltage window is consistent with that of conventional lithium-ion batteries, and it basically does not participate in the electrochemical process in the later stage. It is a lithium supplement additive with broad prospects.
[0005] There are public reports on positive electrode lithium replenishing materials. For example, in a public positive electrode lithium replenishing material, the lithium ion positive electrode lithium replenishing material Li5FeO4 is prepared by the sol-gel method. This material is used as a positive electrode lithium replenishing material for lithium ion batteries and has the characteristics of large charging capacity and small discharge capacity. However, this material has harsh environmental adaptability, large residual alkali on the surface, and is difficult to process.
[0006] In another disclosed positive electrode lithium supplement material, it is a lithium supplement material formed by Co-doped or Co-doped lithium ferrate and carbon material and a sol-gel preparation method. However, during the in-situ coating process of the carbon source at high temperature, the conventional sol-gel is prone to react with the lithium source to partially form non-electrochemically active lithium carbonate, which affects the proportion of the active main body.
[0007] In another disclosed positive electrode lithium supplement material, it is a carbon-coated lithium ferrite material and its preparation method, which is to isolate the external environment by gas phase coating with a carbon source to avoid contact between lithium ferrite and water or carbon dioxide in the air, thereby improving the stability of the material. However, the control of the Li2O component of the material is not explained.
[0008] Research on the relevant publicly available lithium replenishing materials found that although the currently available positive electrode lithium replenishing materials can play a role in replenishing lithium, the currently available publicly reported positive electrode lithium replenishing materials still have shortcomings. For example, in addition to the specific prominent manifestations of low purity and a large amount of residual alkali remaining on the surface, which leads to less than ideal storage stability and processing stability of the existing positive electrode lithium replenishing materials and unsatisfactory lithium replenishing effects, it was further discovered in actual applications that the current lithium replenishing materials still have particles such as density that are difficult to control or unreasonable distribution, which leads to unreasonable distribution and filling in the active layer, which directly leads to excessive stress on the active material particles in the active layer during the electrode manufacturing process such as rolling, resulting in deformation or rupture of the active material particles, thereby affecting the electrochemical properties of the electrode such as gram capacity. Summary of the invention
[0009] The purpose of this application is to overcome the above-mentioned deficiencies of the prior art and to provide a lithium supplement additive and a preparation method and application thereof, so as to solve the technical problems such as deformation or rupture of active material particles contained in the electrode caused by unreasonable distribution of particle density and other factors of the existing lithium supplement additives.
[0010] In order to achieve the above application purpose, the first aspect of the present application provides a lithium supplement additive. The loose bulk density BD of the lithium supplement additive in the present application is 0.45 g / cm 3 -0.85g / cm 3 , tap density TD is 0.8g / cm 3 -1.5g / cm 3 .
[0011] Furthermore, the loose bulk density BD and the tap density TD satisfy: (TD-BD) / TD≤40%.
[0012] Furthermore, the lithium supplement additive includes an iron-based lithium supplement additive.
[0013] Furthermore, the lithium supplement additive is in particle morphology.
[0014] Furthermore, the molecular formula of the iron-based lithium supplement additive is aLiFeO2·bLi2O·cM x O y , wherein a, b, and c in the molecular formula are molar numbers, and a+b≥0.98, c≤0.02; 1.8≤b / a≤2.1; M is a doping element; 1≤y / x≤2.5.
[0015] Furthermore, the lithium supplement additive is a core-shell structure, wherein the core body includes the lithium supplement material, and the surface of the core body is also coated with a hydrophobic encapsulation layer.
[0016] Furthermore, the doping element includes at least one of Ni, Co, Mn, Ti, Al, Cu, V, and Zr.
[0017] Furthermore, the hydrophobic encapsulation layer includes an ion conductor encapsulation layer and / or an electronic conductor encapsulation layer, and the ion conductor encapsulation layer or the electronic conductor encapsulation layer is coated on the surface of the lithium supplementing material with a particle morphology.
[0018] Furthermore, the lithium supplement additive is in particle morphology, and its particle size is 1 μm≤D50≤10 μm, D10 / D50≥0.3, and D90 / D50≤2.
[0019] Furthermore, the BET specific surface area of the lithium supplement additive is 0.5≤BET≤20m 2 / g.
[0020] Furthermore, the resistivity of the lithium supplement additive is 1.0-500Ω / cm.
[0021] In a second aspect of the present application, a method for preparing a lithium supplement additive is provided. The method for preparing a lithium supplement additive of the present application comprises the following steps:
[0022] Provide lithium supplement additive precursors;
[0023] The lithium supplement additive precursor is subjected to a first sintering treatment to generate a lithium supplement additive, and the loose bulk density BD of the lithium supplement additive is 0.45 g / cm 3 -0.85g / cm 3 , tap density TD is 0.8g / cm 3 -1.5g / cm 3 .
[0024] Furthermore, the lithium supplement additive includes an iron-based lithium supplement additive, and the molecular formula of the iron-based lithium supplement additive is aLiFeO2·bLi2O·cM x O y The preparation method of the iron-based lithium supplement additive comprises the following steps:
[0025] According to the molecular formula aLiFeO2·bLi2O·cM x O y An iron source, a lithium source, and a doping element source indicated by M are mixed in a stoichiometric ratio to form a precursor;
[0026] The precursor is sintered to generate a LiFeO2·bLi2O·cM x O y Iron-based lithium supplement additives;
[0027] Furthermore, the temperature of the first sintering treatment is 600-1000° C., and the time is 4-48 hours.
[0028] Furthermore, the first sintering process is to increase the temperature to the sintering process temperature at a heating rate of 10-500° C. / h.
[0029] Furthermore, after the first sintering step, the following second sintering step is also included:
[0030] The product after the first sintering treatment is crushed and classified, and then heated to 600-1000° C. at 0-500° C. / h for heat treatment for 1-20 hours, and then crushed and classified again.
[0031] Furthermore, in the step of mixing the iron source, the lithium source and the doping element source, a carbon source is also added; the total mass of the carbon source and the reactants is 5wt%-50wt%.
[0032] Furthermore, after the step of the first sintering treatment or the second sintering treatment, the method further includes the step of forming a hydrophobic encapsulation layer on the surface of the lithium supplementing material after the first sintering treatment or the second sintering treatment.
[0033] Furthermore, the iron source includes at least one of iron oxide, iron nitrate, iron chloride, iron hydroxide, iron oxalate, iron acetate, and iron hydroxide.
[0034] Furthermore, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, lithium oxide, and lithium oxalate.
[0035] Furthermore, the doping element source includes at least one of Cu, Co, Al, Ti, Fe, V, and Zr sources.
[0036] In a third aspect of the present application, an electrode is provided. The electrode of the present application comprises a current collector and an electrode active layer bonded to the surface of the current collector, wherein the electrode active layer comprises an electrode active material, a lithium supplement additive, a binder and a conductive agent; wherein the lithium supplement additive is the lithium supplement additive of the present application or a lithium supplement additive prepared by the lithium supplement additive preparation method of the present application.
[0037] Furthermore, the electrode is a positive electrode, and the capacity decay rate of the positive electrode stored for 20 hours at an ambient humidity of 25% relative to that stored for 0.5 hours is not more than 3%; the capacity decay rate of the positive electrode stored for 20 hours at an ambient humidity of 10% relative to that stored for 0.5 hours is not more than 1%; wherein the lithium replenishing additive is a positive electrode lithium replenishing additive, which is a core-shell structure, and contains a hydrophobic encapsulation layer coating the core body.
[0038] In a fourth aspect of the present application, a secondary battery is provided. The secondary battery of the present application comprises a positive electrode and a negative electrode, wherein the positive electrode is the electrode of the present application; and the lithium supplement additive contained in the electrode is the positive electrode lithium supplement additive;
[0039] and / or
[0040] The negative electrode is the electrode of the present application; and the lithium supplement additive contained in the electrode is a negative electrode lithium supplement additive.
[0041] Compared with the prior art, this application has the following technical effects:
[0042] The lithium supplement additive of the present application controls BD and TD within a specific range of values, so that the lithium supplement additive of the present application has a specific particle density. When used in the electrode, the lithium supplement additive can be more reasonably distributed in the electrode active layer. Specifically, it can be effectively filled and dispersed between the electrode active material particles to ensure that during the electrode rolling compression process, the stress on the electrode active material particles can be reduced, the electrode active material particles can be prevented from deformation and rupture, and the electrochemical properties of the electrode, such as gram capacity, can be ensured.
[0043] The lithium supplement additive prepared by the preparation method of the lithium supplement additive of the present application has BD and TD in a specific range of values. In addition, the preparation method of the lithium supplement additive can ensure that the structure morphology and particle BD and TD of the prepared lithium supplement additive are stable, giving it stable electrochemical properties, high efficiency, and saving production costs.
[0044] Since the electrode of the present application contains the lithium-supplementing additive of the present application, during the charging and discharging process, the lithium-supplementing additive contained in the electrode can be used as a lithium source to remove lithium during the first cycle of charging, provide abundant lithium ions, and improve the first efficiency of the battery. Moreover, since the lithium-supplementing additive of the present application has a specific range of BD and TD values, it can be reasonably distributed among the electrode active material particles to reduce the stress on the electrode active material particles during the rolling process, avoid or reduce the morphology of the electrode active material particles and the occurrence of undesirable phenomena such as deformation and rupture of the particles, and improve the performance of the electrode's electrochemical properties such as the specific capacity.
[0045] Since the secondary battery of the present application contains the lithium supplement additive of the present application, the electrode cycle performance is good and the internal resistance is low, thereby giving the lithium ion battery of the present application excellent first coulombic efficiency and high gram capacity and cycle performance, long life and stable electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0047] Figure 1 This is a schematic diagram of the structure of the lithium supplement additive in the embodiment of the present application;
[0048] Figure 2 This is a schematic diagram of a process for preparing a lithium supplement additive according to an embodiment of the present application;
[0049] Figure 3 This is a scanning electron microscope image of the lithium supplement additive provided in Example A1;
[0050] Figure 4 A scanning electron microscope image of the lithium supplement additive provided in Example A5;
[0051] Figure 5 A scanning electron microscope image of the lithium supplement additive provided in Comparative Example A1;
[0052] Figure 6 The X-ray diffraction pattern of the lithium supplement additive provided in Example A1;
[0053] Figure 7 The X-ray diffraction pattern of the lithium supplement additive provided in Example A5;
[0054] Figure 8 This is a SEM image of the positive electrode active layer contained in the positive electrode sheet containing the lithium supplement additive in Example A1;
[0055] Fig. 9 This is a SEM image of the positive electrode active layer contained in the positive electrode sheet containing the lithium supplement additive in Comparative Example A1. DETAILED DESCRIPTION
[0056] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0057] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0058] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0059] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0060] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0061] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0062] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0063] In a first aspect, the present invention provides a lithium supplement additive. The particles of the lithium supplement additive satisfy the following requirements: loose bulk density BD (loose bulk density) is 0.45 g / cm 3 -0.85g / cm 3 , tapped density TD (tapped density) is 0.8g / cm 3 -1.5g / cm 3. The BD and TD of the particles of the lithium supplement additive in the embodiment of the present application are controlled within a specific range of values, so that the lithium supplement additive in the embodiment of the present application has a specific particle density characteristic, and when it is used as a lithium supplement additive in an electrode, it can be distributed more reasonably in the electrode active layer, such as being able to effectively fill and disperse between the electrode active material particles. When the electrode is in the rolling process, it can reduce the stress on the electrode active material particles, prevent the electrode active material particles from deformation and rupture, improve the integrity of the morphology of the electrode active material particles, and ensure that the electrode's processing performance and electrochemical properties such as gram capacity are fully utilized. The inventors found in further research that when the BD is greater than 0.85g / cm 3 , TD greater than 1.5g / cm 3 ; When BD is less than 0.45g / cm 3 , TD is less than 0.8g / cm 3 When the above conditions are met, the particle size distribution of the lithium supplement additive will be unreasonable, which will affect the uniformity of its distribution and filling in the electrode active material particles. It will also cause the stress pressure on the electrode active material particles during the electrode preparation process to be uneven or excessive, resulting in deformation or breakage of the electrode active material particles, or the surface quality of the active layer material contained in the prepared electrode sheet is not ideal, thereby reducing the electrochemical performance of the electrode sheet.
[0064] On the premise that the lithium-supplementing additive particles of the embodiment of the present application have the above-mentioned bulk density BD and tap density TD range, in the embodiment, the bulk density BD and tap density TD are further controlled and adjusted so that (TD-BD) / TD≤40%, further ≤35%. Wherein, (TD-BD) / TD is defined as the compression degree of the lithium-supplementing additive particles of the embodiment of the present application. By controlling and adjusting the bulk density BD and tap density TD, the compression degree is controlled within this range, thereby improving the rationality of the filling and dispersion of the lithium-supplementing additive of the embodiment of the present application in the electrode active material particles, making the electrode active material particles bear less stress during the rolling process, further improving the integrity of the morphology of the electrode active material particles in the electrode active layer, avoiding deformation and rupture, and improving the processing performance of the electrode and its electrochemical properties.
[0065] In addition, due to the lithium-rich properties of the lithium-supplementing additive in the embodiment of the present application, it can provide abundant lithium, so that it can act as a "sacrificial agent" during the first cycle of charging, releasing all lithium ions at once as much as possible to replenish the irreversible lithium ions consumed by the formation of the SEI film at the negative electrode, thereby maintaining the abundance of lithium ions in the battery system and improving the first efficiency and overall electrochemical performance of the battery. The type of lithium-supplementing additive in the embodiment of the present application can be a conventional iron-based lithium-supplementing additive, such as an iron-based lithium-supplementing additive, a manganese-based lithium-supplementing additive, etc., and of course it can also be other lithium-supplementing additives.
[0066] In the embodiment, when the lithium supplement additive in the embodiment of the present application is an iron-based lithium supplement additive, the molecular formula of the iron-based lithium supplement additive is aLiFeO2·bLi2O·cM x O y , wherein a, b, and c in the molecular formula are molar numbers, and a+b≥0.98, c≤0.02; 1.8≤b / a≤2.1; M is a doping element; 1≤y / x≤2.5. The iron-based lithium supplement additive shown in the molecular formula is rich in lithium and can provide abundant lithium, and has high purity and low residual alkali content on the surface, giving the iron-based lithium supplement additive high capacity and lithium supplement effect as well as good storage stability and processing stability.
[0067] In the embodiment, the molecular formula is aLiFeO2·bLi2O·cM x O y The doping element M contained in the iron-based lithium supplement additive can combine with the Li2O contained in the iron-based lithium supplement additive to give the iron-based lithium supplement additive full capacity, thereby giving the iron-based lithium supplement additive a high capacity, and improving the kinetic release of lithium ions and improving the interface and structural stability of the iron-based lithium supplement additive. In the embodiment, the doping element includes at least one of Ni, Co, Mn, Ti, Al, Cu, V, and Zr. These metal doping elements can further improve the Li2O combination to improve the capacity of the iron-based lithium supplement additive to further improve the capacity of the iron-based lithium supplement additive, and relative to the anti-fluorite structure of the Fe system, these metal doping elements are more conducive to the kinetic release of lithium ions and improve the interface and structural stability of the iron-based lithium supplement additive.
[0068] The morphology of the lithium supplement additive in each of the above embodiments can be controlled as needed, such as particles or other morphologies. In the embodiments of the present application, the particle morphology is relatively preferred. In addition, when the lithium supplement additive is in the form of particles, it can be a primary particle or a secondary particle. In the embodiment, when the morphology of the lithium supplement additive is particles, its particle size is 1μm≤D50≤10μm.
[0069] In the embodiment, when the lithium supplement additive is in the form of particles, the lithium supplement additive is as follows Figure 1 The core-shell structure shown in the figure specifically includes a core body 10 and a hydrophobic encapsulation layer 20 covering the core body 10. In this case, the core body 10 includes a lithium supplement material, such as but not limited to the above molecular formula aLiFeO2·bLi2O·cM x O yIn this way, the presence of the hydrophobic encapsulation layer 20 can effectively cover the core body 10 containing the lithium supplement material, ensuring that the core body 10 is in direct contact with the environment, such as isolating the adverse factors such as water vapor and carbon dioxide in the environment, thereby ensuring the stability of the lithium supplement material and giving full play to its lithium supplement effect. At the same time, by controlling the material type of the hydrophobic encapsulation layer 20, the residual alkali content of the surface layer of the lithium supplement material contained in the core body 10 can also be reduced, effectively ensuring and improving the storage stability and processing stability of the lithium supplement additive in the embodiment of the present application.
[0070] In a further embodiment, the hydrophobic encapsulation layer 20 can be an ion conductor encapsulation layer or an electronic conductor encapsulation layer or a composite layer structure of an ion conductor encapsulation layer or an electronic conductor encapsulation layer. Among them, the ion conductor encapsulation layer can improve the insertion and extraction effect of lithium ions and the ionic conductivity of lithium ions of the lithium supplement material contained in the core body 10. The electronic conductor encapsulation layer can improve the electronic conductivity of the lithium supplement material contained in the core body 10, improve its electrical conductivity, stimulate the gram capacity of the lithium supplement additive in the embodiment of the present application, and realize efficient lithium supplementation in a true sense.
[0071] When the hydrophobic encapsulation layer 20 includes an ion conductor encapsulation layer, the material of the ion conductor encapsulation layer may be a material that is conducive to improving ion conductivity, such as at least one of a perovskite type, a NASICON type, and a garnet type, but not limited thereto. When the hydrophobic encapsulation layer 20 includes an electronic conductor encapsulation layer, the material of the electronic conductor encapsulation layer may be a material that is conducive to improving electronic conductivity, such as at least one of a carbon material, a conductive oxide, and a conductive organic matter, but not limited thereto.
[0072] The thickness of the hydrophobic encapsulation layer 20 can be adjusted according to the needs of practical applications. For example, in the embodiment, the thickness of the hydrophobic encapsulation layer 20 is 1-200 nm. In other embodiments, the hydrophobic encapsulation layer 20 can be controlled to account for 1wt%-5wt% of the total mass of the lithium supplement additive. Controlling the thickness and content of the hydrophobic encapsulation layer 20 within this range can improve the compactness of the hydrophobic encapsulation layer 20, and reduce the residual alkali content remaining on the surface of the lithium supplement material contained in the core body 10 to further improve the storage stability and processing stability of the lithium supplement additive in the embodiment of the present application, while improving the ionic and / or electronic conductivity of the lithium supplement additive in the embodiment of the present application.
[0073] In addition, the hydrophobic encapsulation layer 20 may further include other functional layers as required, and the types of other functional layers may be flexibly selected as required.
[0074] In the above-mentioned embodiments, the lithium supplement additive may be in the form of particles, or other forms. In the embodiments, when the lithium supplement additive is in the form of particles, the particle size of the lithium supplement additive is: 1μm≤D50≤10μm, D10 / D50≥0.3, D90 / D50≤2. The inventors found in their research that when the D50 of the lithium supplement additive is less than 1μm, the particles of the lithium supplement additive are small, the specific surface area is too large, and the high activity can easily cause performance failure and reduction. When the D50 of the lithium supplement additive is greater than 10μm, the particles are too large, and the lithium ion migration path is too long, causing kinetic polarization problems and insufficient capacity. Therefore, in the embodiments, the specific surface area of the lithium supplement additive is 0.5≤BET≤20m 2 / g. The particle size range and specific surface area of the lithium supplement additive enable the lithium supplement additive to fully exert its above-mentioned functions such as lithium supplement and high capacity, and improve its dispersibility.
[0075] According to the test, the resistivity of the lithium supplement additive in the above embodiments can be reduced to 1.0-1000Ω / cm, especially Figure 1 The lithium supplement additive contains a hydrophobic encapsulation layer 20, and when the hydrophobic encapsulation layer 20 is an electronic encapsulation layer, it has a small resistivity and good electrical conductivity, which can effectively stimulate the gram capacity of the lithium supplement additive.
[0076] Accordingly, the present application also provides a method for preparing the lithium supplement additive described above. The process flow of the method for preparing the lithium supplement additive is as follows: Figure 2 As shown, the preparation method thereof comprises the following steps:
[0077] Step S01: providing a lithium supplement additive precursor;
[0078] Step S02: performing a first sintering process on the lithium supplement additive precursor to generate the lithium supplement additive.
[0079] The lithium supplement additive precursor in step S01 should be the precursor of the lithium supplement additive in the above application, such as the iron-based lithium supplement additive precursor, manganese-based lithium supplement additive precursor, etc. The iron-based lithium supplement additive precursor can be aLiFeO2·bLi2O·cM in the above molecular formula. x O y The iron-based lithium supplement additive precursor is shown.
[0080] In step S02, after the precursor is subjected to the first sintering treatment, the lithium supplement additive described above is formed, and the lithium supplement additive is endowed with lithium-rich, high purity, low residual alkali content on the surface, and has a specific range of BD and TD. In addition, the preparation method of the lithium supplement additive can ensure that the structure and morphology of the prepared lithium supplement additive and the stability of the particle BD and TD are stable, giving it high capacity and lithium supplement effect as well as good storage stability and processing stability.
[0081] In an embodiment, the temperature of the first sintering treatment can be 600-1000°C, and the time is 4-48h. In a further embodiment, the first sintering treatment is heated to the first sintering treatment temperature at a heating rate of 10-500°C / h. By controlling and optimizing the sintering temperature and heating rate, the purity of the lithium supplement additive formed by sintering can be improved, and the residual alkali content remaining on its surface can be reduced. More importantly, the particle size of the generated lithium supplement additive can be controlled, such as giving the lithium supplement additive BD and TD with the above-mentioned specific range values, thereby improving the lithium supplement additive with high capacity and lithium supplement effect as well as good storage stability and processing stability.
[0082] As in the embodiment, when the lithium supplement additive precursor in step S01 is aLiFeO2·bLi2O·cM in the above molecular formula x O y When the iron-based lithium supplement additive precursor is shown, its preparation method includes the following steps:
[0083] Step S011: According to the molecular formula aLiFeO2·bLi2O·cM x O y The iron source, lithium source and doping element source are mixed in a stoichiometric ratio to form aLiFeO2·bLi2O·cM x O y Precursor;
[0084] Step S012: aLiFeO2·bLi2O·cM x O y The precursor is subjected to the first sintering treatment to generate a LiFeO2·bLi2O·cM x O y Iron-based lithium supplement additive.
[0085] The lithium supplement additive generated by the first sintering treatment is particularly aLiFeO2·bLi2O·cM x O y The lithium supplement additive is rich in lithium and has high purity, and the residual alkali content on the surface is low. It also has BD and TD with specific range values, giving aLiFeO2·bLi2O·cM x O y Lithium replenishing additives have high capacity and lithium replenishing effect as well as good storage stability and processing stability.
[0086] Wherein, in the molecular formula in step S011, aLiFeO2·bLi2O·cM x O yThe meanings of a, b, c, M, y, and x are the same as above. The molecular formula of the iron-based lithium supplement additive is aLiFeO2·bLi2O·cM x O y As shown. Therefore, the stoichiometric ratio of elements in step S011 can be a molar ratio, or a mass ratio converted according to the molar ratio. In the embodiment, the iron source includes at least one of iron oxide, iron nitrate, iron chloride, iron hydroxide, iron acetate, iron hydroxide, and iron oxalate; the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, lithium oxide, and lithium oxalate; and the doping element source includes at least one of Cu, Co, Al, Ti, Fe, V, and Zr sources. These iron sources, lithium sources, and doping element sources can be effectively mixed evenly after being mixed in proportion, and the cost of these raw materials is low, which effectively reduces the cost of iron-based lithium supplement additives. In addition, the doping element source can be selected and the type adjusted as needed. In a specific embodiment, the Cu source can be at least one of copper oxide, copper nitrate, copper chloride, copper hydroxide, copper acetate, copper hydroxide, and copper carbonate, the Co source can be at least one of cobalt oxide, cobalt nitrate, cobalt chloride, cobalt hydroxide, cobalt acetate, cobalt hydroxide, and cobalt carbonate, the Al source can be at least one of aluminum oxide, aluminum nitrate, aluminum chloride, aluminum hydroxide, aluminum acetate, and aluminum hydroxide, the Ti source can be at least one of titanium dioxide and titanium chloride, the Ni source can be at least one of nickel oxide, nickel nitrate, nickel chloride, nickel hydroxide, nickel acetate, and nickel hydroxide, the V source can be at least one of vanadium pentoxide and vanadium nitrate, and the Zr source can be at least one of zirconium oxide, zirconium nitrate, zirconium chloride, zirconium hydroxide, zirconium acetate, zirconium hydroxide, and zirconium carbonate.
[0087] The mixing treatment in step S011 is to make the source materials mix evenly. Therefore, the mixing treatment can be a conventional mixing treatment, and ideally a grinding treatment. On the premise of achieving uniform mixing of the source materials, the particle size of each source compound is refined to further improve the mixing uniformity of the source materials, thereby improving the stability of the structure and electrochemical performance of the iron-based lithium supplement additive.
[0088] In a further embodiment, a carbon source is also added in the mixing process of the iron source, lithium source, and doping element source in step S011. By directly adding a carbon source to the precursor, the sintering treatment conditions in step S012 can be controlled, such as controlling the sintering process in a non-oxygen environment, so that the carbon source is in situ coated on the surface of the iron-based material particles formed by sintering, and a carbon coating layer is formed on the surface of the iron-based material particles. The carbon coating layer generated at this time is the electronic packaging layer of the hydrophobic encapsulation layer 20 contained in the above lithium supplement additive. In the embodiment, the total mass of the carbon source and the reactant is 5wt%-50wt%. In a specific embodiment, the carbon source includes at least one of citric acid, succinic acid, glucose, lactose, sucrose, starch, and polyethylene glycol. By selecting the amount and type of the carbon source, the amount of carbon coating and the quality of the carbon coating layer formed are controlled.
[0089] In step S012, aLiFeO2·bLi2O·cM x O y After the precursor is subjected to the first sintering treatment, aLiFeO2·bLi2O·cM in the molecular formula is formed. x O y Iron-based lithium-replenishing additive. In the embodiment, the first sintering treatment is the first sintering treatment in step S02 above, such as the sintering treatment temperature is 600-1000°C, and the time is 4-48h. In a further embodiment, the first sintering treatment is heated to the first sintering treatment temperature at a heating rate of 10-500°C / h. By controlling and optimizing the sintering temperature and heating rate, the purity of the iron-based lithium-replenishing additive formed by sintering can be improved, the residual alkali content remaining on its surface can be reduced, and the lithium-replenishing additive has a high capacity and lithium-replenishing effect as well as good storage stability and processing stability.
[0090] After the first sintering step in step S02, the following second sintering step is also included:
[0091] The product after the first sintering treatment is crushed and then heated to 600-1000° C. at 0-500° C. / h for heat treatment for 1-20 hours, and then crushed and classified again.
[0092] The second sintering treatment can be used to sinter the reactants that did not participate in the reaction into the expected target products, improve the overall electrical properties of the composite material and reduce the residual alkali. In principle, the more sintering times, the higher the purity. Therefore, without considering the cost, the second sintering treatment can be multiple times, that is, more than twice.
[0093] The lithium supplement additive generated after the first sintering treatment or the further second sintering treatment may be primary particles or secondary particles.
[0094] In a further embodiment, after step S02, specifically after the first sintering process or the second sintering process, the following is further included: Figure 2 Step S03 shown in:
[0095] A hydrophobic encapsulation layer is formed on the surface of the lithium supplement material after the first sintering treatment or the second sintering treatment, that is, a hydrophobic encapsulation layer is formed. Figure 1 The hydrophobic encapsulation layer 20 is provided in the embodiment of the present invention.
[0096] A hydrophobic encapsulation layer is formed on the surface of the lithium supplement material to achieve surface modification of the lithium supplement material, forming a dense coating layer to isolate the lithium supplement material from direct contact with the environment, and can also reduce the residual alkali content remaining on the surface of the lithium supplement material, effectively ensuring and improving the storage stability and processing stability of the lithium supplement additive; at the same time, it effectively improves the ionic and / or electronic conductivity of the lithium supplement additive, giving the lithium supplement additive a high conductive property, stimulating the gram capacity of the lithium supplement additive, and realizing truly efficient lithium supplementation.
[0097] The method for forming a hydrophobic encapsulation layer in step S03 can be to flexibly select appropriate methods to form each layer structure according to the structure of the hydrophobic encapsulation layer and the type of material of the layer structure. For example, in-situ coating and then sintering treatment can be selected according to the characteristics of the layer structure material, or other functional layers can be formed by physical deposition, chemical deposition and other methods.
[0098] By controlling the amount of the hydrophobic encapsulation layer formed in step S03, the thickness of the hydrophobic encapsulation layer is controlled within the above-mentioned thickness range, or the hydrophobic encapsulation layer is further controlled to account for 1wt%-5wt% of the total mass of the lithium supplementing additive, thereby giving full play to the above-mentioned role of the hydrophobic encapsulation layer.
[0099] Therefore, the preparation method of the lithium supplement additive can effectively ensure that the prepared lithium supplement additive is rich in lithium, has high purity, has low residual alkali content on the surface, and the generated lithium supplement additive particles have BD and TD values within a specific range. Moreover, the preparation method of the lithium supplement additive can ensure that the structure and electrochemical performance of the prepared lithium supplement additive are stable, efficient, and save production costs.
[0100] On the other hand, the embodiment of the present application provides a composite lithium supplement additive. The composite lithium supplement additive of the embodiment of the present application includes the lithium supplement additive of the embodiment of the above text application, and of course, it can further include other additives suitable for the electrode, or auxiliary additives that are conducive to giving full play to the lithium supplement effect of the lithium supplement additive of the embodiment of the above text application. When other additives are contained, the ratio between the lithium supplement additive and the additive can be adjusted according to the needs of practical applications. Since the electrode lithium supplement additive contains the lithium supplement additive of the embodiment of the above text application, the electrode lithium supplement additive can be used as a lithium source in the first cycle of charging and discharging as a "sacrificial agent" to supplement the irreversible lithium ions consumed by the formation of SEI film at the negative electrode, thereby maintaining the abundance of lithium ions in the battery system and improving the first efficiency of the battery. Moreover, after the granular lithium supplement additive with specific BD and TD values is mixed with the electrode active material, it can effectively reduce the stress borne by the electrode active material particles in the rolling process, avoid or reduce the morphology of the electrode active material particles and the occurrence of undesirable phenomena such as deformation and rupture of the particles, and give full play to the electrochemical properties of the electrode active material such as gram capacity.
[0101] On the other hand, the embodiment of the present application provides an electrode material. The electrode material of the embodiment of the present application includes an electrode active material and a lithium supplement additive. Among them, the lithium supplement additive is the lithium supplement additive of the above embodiment of the present application or the above composite lithium supplement additive. Of course, the electrode material can also include electrode materials in the field of lithium-ion batteries. Of course, the electrode properties of the electrode active material contained in the electrode material are consistent with the electrode properties of the lithium supplement additive. If the electrode material is a positive electrode material, it includes a positive electrode active material and a positive electrode lithium supplement additive; if the electrode material is a negative electrode material, it includes a negative electrode active material and a negative electrode lithium supplement additive.
[0102] Since the electrode material of the embodiment of the present application contains the above-mentioned lithium-replenishing additive of the embodiment of the present application. Therefore, during the process of charging and discharging, the lithium-replenishing additive contained in the electrode material can be used as a lithium source as a "sacrificial agent" during the first cycle of charging to replenish the irreversible lithium ions consumed by the formation of the SEI film at the negative electrode, thereby maintaining the abundance of lithium ions in the battery system and improving the initial efficiency and overall electrochemical performance of the battery. Moreover, the lithium-replenishing additive contained has specific BD and TD values. After being mixed with the electrode active material, it can effectively reduce the stress on the electrode active material particles during the rolling process, avoid or reduce the morphology of the electrode active material particles and the occurrence of adverse phenomena such as deformation and rupture of the particles, and give full play to the electrochemical properties of the electrode active material particles.
[0103] In the embodiment, the content of the lithium supplement additive in the electrode material is 0.5wt%-10wt%. By controlling and optimizing the content of the lithium supplement additive in the electrode material, the lithium supplement additive can fully exert its above function.
[0104] At the same time, based on the electrode material of the embodiment of the present application, the embodiment of the present application also provides an electrode and a secondary battery containing the electrode of the embodiment of the present application.
[0105] The active material contained in the electrode is the electrode material of the embodiment of the present application. The electrode can be a conventional positive electrode of a secondary battery or a negative electrode. For example, the positive electrode or negative electrode includes a current collector and an electrode active layer bonded to the surface of the current collector, and the electrode active layer contains the above electrode material, that is, includes the electrode active material and the above lithium supplement additive or composite lithium supplement additive.
[0106] For example, when the electrode is a positive electrode, the positive electrode current collector contained in the positive electrode includes but is not limited to any one of copper foil and aluminum foil. The positive electrode active layer contains the electrode material (positive electrode material) of the above-mentioned application embodiment, that is, it contains the positive electrode active material and the lithium supplement additive of the above-mentioned application embodiment or the composite lithium supplement additive of the above-mentioned application embodiment. In the embodiment, the mass content of the lithium supplement additive, that is, the lithium supplement additive of the above-mentioned application embodiment in the positive electrode active layer is 0.5wt%-10wt%; specifically, it can be 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc., preferably 1wt% to 6wt%, and more preferably 3wt%-6wt%.
[0107] The positive electrode active layer includes, in addition to the lithium supplement additive, a positive electrode active material, a binder and a conductive agent. In the embodiment, the positive electrode active material includes at least one of lithium cobalt oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium manganate, nickel cobalt manganate, and lithium nickel manganate. In the embodiment, the content of the binder in the positive electrode active layer is 0.5wt%-3wt%. In a specific embodiment, the binder includes one or more of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives. In the embodiment, the content of the conductive agent in the positive electrode active layer is 0.2wt%-5wt%. In a specific embodiment, the conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60, and carbon nanotubes. In the embodiment, the positive electrode is prepared by mixing the positive electrode active material, lithium supplement additive, conductive agent and binder to obtain positive electrode slurry, coating the positive electrode slurry on the current collector, and preparing the positive electrode sheet through drying, rolling, die cutting and other steps.
[0108] Since the electrode of the embodiment of the present application is the above-mentioned positive electrode, it contains the lithium supplement additive of the embodiment of the text application, that is, the lithium supplement additive contained in the positive electrode has a loose bulk density and a tap density range of the above-mentioned specific range values. During the positive electrode roller compression process, it and the positive electrode active material can reduce the stress borne by the positive electrode active material particles, effectively prevent the deformation and rupture of the electrode active material particles, and can also improve the dispersion performance of the lithium supplement additive and improve the quality of the positive electrode active layer.
[0109] In the embodiment, when the lithium supplement additive contained in the positive electrode is the core-shell structure described above, that is, it includes a core body and a hydrophobic encapsulation layer coated on the core body, it also gives the positive electrode good storage and electrochemical performance stability. As tested, the capacity of the positive electrode containing the lithium supplement additive of the core-shell structure above is stored at an ambient humidity of 25% for 20 hours relative to the capacity attenuation rate of 0.5 hours is not more than 3%, and further not more than 2%; the capacity stored for 20 hours at an ambient humidity of 10% is stored at a capacity attenuation rate of 0.5 hours is not more than 1%, and further not more than 0.5%. This reflects that the lithium supplement additive of the embodiment of the present application having the above core-shell structure, that is, containing a hydrophobic encapsulation layer, has the above-mentioned loose bulk density and tap density range, and the positive electrode sheet formed by it has excellent storage and high lithium supplement effect and lithium supplement stability. Similarly, when the lithium supplement additive above is further a lithium supplement additive of a core-shell structure as a negative electrode lithium supplement additive, it can also play the role of the positive electrode lithium supplement additive in the negative electrode as mentioned above in the positive electrode. This shows that the lithium supplement additive in the embodiment of the above application can be more reasonably distributed in the electrode active layer when used in the electrode, specifically, it can be effectively filled and dispersed between the electrode active material particles, ensuring that the stress on the electrode active material particles can be reduced during the electrode rolling and compression process, and effectively preventing the electrode active material particles from deforming and rupturing. Ideally, the lithium supplement additive and the electrode in the above application are stored in a dry, oxygen-free favorable environment such as a vacuum environment to maximize the electrochemical performance of the lithium supplement additive and the electrode in the above application.
[0110] Then, the lithium ion battery of the embodiment of the present application contains the above-mentioned electrode, such as the above-mentioned positive electrode. Of course, the lithium ion battery of the embodiment of the present application also has the necessary components such as the negative electrode, the separator and the electrolyte required by the lithium ion battery. Among them, the negative electrode can also contain the lithium supplement additive of the embodiment of the present application suitable for the negative electrode application.
[0111] Since the electrode contains the lithium-replenishing additive of the above-mentioned application embodiment, during the first cycle charging process of the lithium-ion battery of the present application embodiment, the lithium-replenishing additive of the above-mentioned application embodiment contained in the electrode acts as a "sacrificial agent" to release all lithium ions at once as much as possible to replenish the irreversible lithium ions consumed by the formation of the SEI film at the negative electrode, thereby maintaining the abundance of lithium ions in the lithium-ion battery system of the present application embodiment, and improving the overall electrochemical properties such as the first effect, capacity, and cycle performance of the lithium-ion battery of the present application embodiment. Moreover, during the rolling process of the electrode, the lithium-replenishing additive and the electrode active material can be more reasonably distributed, thereby effectively reducing the stress on the electrode active material particles, avoiding or reducing the morphology of the electrode active material particles and the occurrence of undesirable phenomena such as deformation and rupture of the particles, and giving full play to the electrochemical properties of the electrode active material particles.
[0112] The lithium supplement additive of the present application and its preparation method and application are illustrated below through a number of specific embodiments.
[0113] 1. Lithium supplement additive and preparation method thereof:
[0114] Example A1
[0115] This embodiment provides a lithium supplement additive and a preparation method thereof. The structure of the lithium supplement additive is as follows: Figure 1 As shown, it includes LiFeO2·1.99Li2O lithium-rich iron-based material and a carbon coating layer coating the lithium-rich iron-based material.
[0116] The preparation method of the lithium supplement additive in this embodiment comprises the following steps:
[0117] S1. Fe(NO3)3·9H2O and LiNO3 were added to a 10wt% citric acid aqueous solution at a molar ratio of 1:5.02, mixed well, spray dried at 250°C, and crushed to obtain a precursor;
[0118] S2. In a nitrogen atmosphere, the precursor was heated to 800°C at a rate of 300°C / h and kept at this temperature for 12 h. After cooling, the product was mechanically crushed and accurately graded to obtain in-situ carbon-coated LiFeO2·2.01Li2O powder.
[0119] The average particle size of the in-situ carbon-coated LiFeO2·2.01Li2O powder was 3.4 μm, the thickness of the carbon coating layer was 35 nm, and the BET value was 10.3 nm. 2 / g.
[0120] Example A2
[0121] This embodiment provides a lithium supplement additive and a preparation method thereof. The structure of the lithium supplement additive is as follows: Figure 1As shown, it includes LiFeO2·2.01Li2O·0.01Al2O3 lithium-rich iron-based material and a carbon coating layer coating the lithium-rich iron-based material.
[0122] The preparation method of the lithium supplement additive in this embodiment comprises the following steps:
[0123] S1. Fe(NO3)3·9H2O, LiNO3, and Al(NO3)3 were added to a 10wt% citric acid aqueous solution at a molar ratio of 1:5.02:0.02, mixed well, spray dried at 250°C, and crushed to obtain a precursor;
[0124] S2. In a nitrogen atmosphere, the precursor was heated to 850°C at a rate of 300°C / h and kept at this temperature for 15 h. After cooling, the product was mechanically crushed and precisely graded to obtain in-situ carbon-coated LiFeO2·2.01Li2O·0.01Al2O3 powder.
[0125] The average particle size of the in-situ carbon-coated LiFeO2·1.99Li2O·0.005Al2O3 powder was 4.9 μm, the thickness of the carbon coating layer was 35 nm, and the BET value was 4.2 nm. 2 / g.
[0126] Example A3
[0127] This embodiment provides a lithium supplement additive and a preparation method thereof. The structure of the lithium supplement additive is as follows: Figure 1 As shown, it includes LiFeO2·2.05Li2O·0.015CoO lithium-rich iron-based material and a carbon coating layer coating the lithium-rich iron-based material.
[0128] The preparation method of the lithium supplement additive in this embodiment comprises the following steps:
[0129] S1. Fe(NO3)3·9H2O, LiOH and Co(NO3)3 were added into a 15wt% PVP aqueous solution at a molar ratio of 1:5.1:0.015, mixed well, spray dried at 250°C and crushed to obtain a precursor;
[0130] S2. In a nitrogen atmosphere, the precursor was heated to 800°C at a rate of 300°C / h and kept at this temperature for 20 h. After cooling, the product was mechanically crushed and precisely graded to obtain in-situ carbon-coated LiFeO2·2.05Li2O·0.015CoO powder.
[0131] The average particle size of the in-situ carbon-coated LiFeO2·2.05Li2O·0.015CoO powder was 6.7 μm, the thickness of the carbon coating layer was 21 nm, and the BET was 1.5 nm. 2 / g.
[0132] Example A4
[0133] This embodiment provides a lithium supplement additive and a preparation method thereof. The structure of the lithium supplement additive is as follows: Figure 1 As shown, it includes LiFeO2·2.05Li2O·0.015ZrO2 lithium-rich iron-based material and a carbon coating layer coating the lithium-rich iron-based material.
[0134] The preparation method of the lithium supplement additive in this embodiment comprises the following steps:
[0135] S1. FeCl3, Li2CO3, and ZrCl4 were added to a 20 wt% polyethylene glycol aqueous solution in a molar ratio of 1:2.55:0.015, mixed well, spray dried at 250°C, and crushed to obtain a precursor;
[0136] S2. In a nitrogen atmosphere, the precursor was heated to 750°C at a rate of 100°C / h and kept at this temperature for 20 h. After cooling, the product was mechanically crushed and precisely graded to obtain in-situ carbon-coated LiFeO2·2.05Li2O·0.015ZrO2 powder.
[0137] The average particle size of the in-situ carbon-coated LiFeO2·2.05Li2O·0.015ZrO2 powder was 4.9 μm, the thickness of the carbon coating layer was 31 nm, and the BET was 2.4 nm. 2 / g.
[0138] Example A5
[0139] This embodiment provides a lithium supplement additive and a preparation method thereof. The structure of the lithium supplement additive is as follows: Figure 1 As shown, it includes LiFeO2·2.05Li2O·0.015CuO lithium-rich iron-based material and a carbon coating layer coating the lithium-rich iron-based material.
[0140] The preparation method of the lithium supplement additive in this embodiment comprises the following steps:
[0141] S1. Fe(NO3)3·9H2O, LiOH, and Cu(NO3)3 were added to a 40wt% grape seed solution in a molar ratio of 1:5.1:0.015, mixed well, spray dried at 250°C, and crushed to obtain a precursor;
[0142] S2. In a nitrogen atmosphere, the precursor was heated to 850°C at a rate of 200°C / h and kept at this temperature for 10 h. After cooling, the product was mechanically crushed and precisely graded to obtain in-situ carbon-coated LiFeO2·2.05Li2O·0.015CuO powder.
[0143] The average particle size of the in-situ carbon-coated LiFeO2·2.05Li2O·0.015CuO powder was 4.9 μm, the thickness of the carbon coating layer was 18 nm, and the BET value was 3.1 nm. 2 / g.
[0144] Example A6
[0145] This embodiment provides a lithium supplement additive and a preparation method thereof. The lithium supplement additive is LiFeO2·1.99Li2O.
[0146] The preparation method of the lithium supplement additive comprises the following steps:
[0147] Fe(NO3)3·9H2O and LiNO3 were added to a 10wt% citric acid aqueous solution at a molar ratio of 1:4.98 and mixed thoroughly. The mixture was spray dried at 280°C and crushed. In an air atmosphere, the temperature was raised to 850°C at a rate of 300°C / h and kept at this temperature for 15h. After cooling, the product was mechanically crushed through a 400-mesh sieve without precise classification to obtain LiFeO2·1.99Li2O powder with an average particle size of 11μm. The loose bulk density BD of the material is 0.58g / cm 3 , the tap density TD is 0.87g / cm 3 . Compression degree (TD-BD) / TD=34.5%.
[0148] Example A7
[0149] Existing LCO materials were directly obtained and, through a controller preparation method, their BD and TD were controlled as shown in Table 4 below.
[0150] Example A8
[0151] This embodiment provides a lithium supplement additive and a preparation method thereof. Compared with Example A1, the loose bulk density BD of the lithium-rich iron-based material LiFeO2·1.99Li2O in this comparative example is 0.48 g / cm 3 , tap density TD is 0.80g / cm 3 .Compression degree (TD-BD) / TD=40.0%.
[0152] Comparative Example A1
[0153] This embodiment provides a lithium supplement additive and a preparation method thereof. Compared with Example A1, the loose bulk density BD of the lithium-rich iron-based material LiFeO2·1.99Li2O in this comparative example is 0.87 g / cm 3 , tap density TD is 1.55g / cm 3 . Compression degree (TD-BD) / TD=43.9%.
[0154] Comparative Example A2
[0155] This comparative example provides a lithium supplement additive and a preparation method thereof. Compared with Example A1, the loose bulk density BD of the lithium-rich iron-based material LiFeO2·1.99Li2O in this comparative example is 0.40 g / cm 3 , tap density TD is 0.75g / cm 3 . Compression degree (TD-BD) / TD=46.7%.
[0156] Comparative Example A3
[0157] This comparative example provides a lithium-rich iron-based material and a preparation method thereof. Compared with Example A1, the loose bulk density BD of the lithium-rich iron-based material LiFeO2·1.99Li2O in this comparative example is 0.74 g / cm 3 , tap density TD is 1.55g / cm 3 . Compression degree (TD-BD) / TD=52.3%.
[0158] 2. Lithium-ion battery example:
[0159] The lithium supplement additives provided in the above-mentioned Examples A1 to A8 and the lithium supplement additives provided in Comparative Examples A1 to A3 are respectively prepared into positive electrodes and assembled into lithium ion batteries according to the following methods:
[0160] Positive electrode: LCO positive electrode active material, lithium supplement additive, polyvinylidene fluoride, SP-Li and CNT are mixed in a mass ratio of 96:2:1.5:0.5:0.5, and ball milled to obtain positive electrode slurry. The positive electrode slurry is coated on the surface of aluminum foil, pressed against a pair of rollers, and vacuum dried overnight at 110°C to obtain a positive electrode sheet; wherein the lithium supplement additive is the lithium supplement additive provided in the above-mentioned Examples A1 to A8 and the lithium supplement additive provided in Comparative Examples A1 to A3, respectively.
[0161] Negative electrode: lithium metal sheet;
[0162] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF6 was added to form an electrolyte, the concentration of LiPF6 was 1 mol / L;
[0163] Diaphragm: Polypropylene microporous separator.
[0164] Lithium-ion battery assembly: Lithium-ion batteries are assembled in an inert atmosphere glove box in the order of lithium metal sheet-diaphragm-electrolyte-positive electrode sheet.
[0165] Related characteristics test
[0166] 1. Characterization of lithium supplement additives:
[0167] 1.1 Scanning electron microscope (SEM) was used to characterize the lithium supplement additives of Example A1, Example A5 and Example A6. Figure 3 , Figure 4 and Figure 5 ,in, Figure 3 This is a scanning electron microscope image of the lithium supplement additive provided in Example A1, Figure 4 This is a scanning electron microscope image of the lithium supplement additive provided in Example A5, Figure 5 This is a scanning electron microscope image of the lithium supplement additive provided in Example A6. Figure 3 It can be seen that the in-situ carbon-coated lithium supplement additive of Example A1 has a large number of irregular particles and a relatively rough interface. Figure 4 It can be seen that the surface of the lithium supplement additive in Example A5 is relatively smooth. Figure 5 It was found that the interface of the uncoated lithium supplement additive was also relatively rough.
[0168] 1.2 X-ray diffraction characterization of the lithium supplement additives of Example A1 and Example A5 is performed, see Figure 6 and Figure 7 ,in, Figure 6 This is the X-ray diffraction pattern of the lithium supplement additive provided in Example A1 of the present application, Figure 7 This is the X-ray diffraction pattern of the lithium supplement additive provided in Example A5 of the present application. Figure 6 It can be seen that the lithium supplement additive has a diffraction peak of LiFeO2 in addition to the main peak of Li5FeO4. Figure 7 It can be seen that the lithium supplement additive is mainly Li5FeO4, with less LiFeO2.
[0169] 1.3 Scanning electron microscope characterization of the positive electrode active layer of the positive electrode sheet prepared by roller pressing:
[0170] The positive electrode active layers contained in the positive electrode sheets prepared according to the above method were analyzed by scanning electron microscope (SEM), wherein the positive electrode active layers contained in the positive electrode sheets containing the lithium supplement additives in Example A1 and Comparative Example A1 were SEM images of 8 and Fig. 9 shown.
[0171] Depend on Figure 8 It can be seen that the particles in the positive electrode active layer containing the lithium supplement additive of Example A1 did not crack. Further SEM analysis of the positive electrode active layer containing the lithium supplement additives of Examples A2 to A8 showed that the particles in the positive electrode active layer contained in each positive electrode sheet also did not crack. Fig. 9It can be seen that the particles in the positive electrode active layer containing the lithium supplement additive of comparative example A1 have obvious cracking. Further SEM analysis of the positive electrode active layers of the lithium supplement additives of other comparative examples shows that the particles in the positive electrode active layers also have obvious cracking.
[0172] It can be seen that the present invention controls the particle BD and TD of the lithium supplement additive to 0.45 g / cm 3 -0.85g / cm 3 and 0.8g / cm 3 -1.5g / cm 3 The range value can effectively fill and disperse between the positive electrode active material particles. When the positive electrode is in the rolling process, it can reduce the stress on the positive electrode active material particles and prevent the positive electrode active material particles from deformation and rupture, thereby ensuring that the positive electrode sheet's gram capacity is fully utilized.
[0173] 2 Moisture resistance test of positive electrode:
[0174] In order to further evaluate the moisture resistance of the above lithium supplement material, the positive electrode in the above lithium ion battery embodiment was placed at different humidity (25%, 20%, 10%) for different time periods and then the specific capacity of each positive electrode was checked. The results of the positive electrode containing the lithium supplement additive of Example A1 and the positive electrode containing the lithium supplement additive of Comparative Example A1 are shown in Tables 1 to 3, respectively. As shown in Tables 1 to 3, the specific capacity of the positive electrode sheet prepared by the lithium supplement additive of Example A1 of the present application changes when the battery is stored at different humidity, but the change is not large. In particular, when the humidity is 10%, the specific capacity after 20 hours of placement is almost attenuated relative to that after 0.5 hours of placement, that is, the attenuation rate is less than 0.2% (Note: Attenuation rate = (1-specific capacity after 20 hours of placement / specific capacity after 0.5 hours of placement) * 100%. Under the same conditions, the specific capacity of the positive electrode sheet prepared by the positive electrode lithium supplement additive of Comparative Example A1 is significantly lower than that of Example A1, and the attenuation amplitude is greater than that of Example A1, as shown in Table 1.
[0175] Table 1
[0176]
[0177] Table 2
[0178]
[0179] Table 3
[0180]
[0181]
[0182] 3. Electrochemical performance of lithium-ion batteries:
[0183] The electrochemical performance of lithium secondary batteries containing the lithium supplement additives of Examples A1 to A8 and the lithium supplement additives of Comparative Examples A1 to A3 was tested, and the test conditions were: the assembled battery was placed at room temperature for 24 hours and then charged and discharged, and the charge and discharge voltage was 2.7V-4.5V. The electrochemical performance of lithium secondary batteries containing the lithium supplement additives of Examples A1 to A8 and the lithium supplement additives of Comparative Examples A1 to A3 is shown in Table 4 below.
[0184] As can be seen from Table 4, the positive electrode slurry prepared with the lithium supplement additive containing the carbon coating structure in Examples A1 to A8 of the present application does not have a jelly phenomenon and is easy to coat. When it is added to a lithium secondary battery, the positive electrode can have a higher initial gram capacity and a lower initial efficiency, thereby compensating for the reduction in energy density caused by the irreversible lithium loss of the first negative electrode. At the same time, it can be seen from Table 4 that when the content of the carbon coating increases, the proportion of the main electrochemical activity of the lithium ion battery decreases, and the capacity is also reduced. Therefore, in the embodiments of the present application, the thickness of the carbon coating of the lithium supplement additive is not easy to be too thick or the content is not easy to be too high, which will reduce the lithium supplement effect of the lithium supplement additive.
[0185] It can be seen from the comparative example experiments that the lithium supplement additives of Example A6 and Example A7 are not coated, and absorb water during the preparation of the positive electrode slurry to form jelly, which is not conducive to the coating of the positive electrode slurry.
[0186] At the same time, the loose bulk density BD of the particles of the lithium supplement additive in the embodiment of the present application is controlled at 0.45 g / cm 3 -0.85g / cm 3 The tap density TD is controlled at 0.8g / cm 3 -1.5g / cm 3 The range can reduce the stress on the positive electrode active material particles and prevent the positive electrode active material particles from deformation and rupture, thereby ensuring the full utilization of the positive electrode sheet capacity. However, the comparison example is not distinguished within this range, resulting in the rupture of the positive electrode material particles in the positive electrode active layer, thereby affecting the full utilization of the positive electrode sheet capacity.
[0187] Table 4
[0188]
[0189] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A lithium supplement additive, characterized in that: The loose bulk density BD of the lithium supplement additive is 0.45 g / cm 3 -0.85 g / cm 3 , the tap density TD is 0.8 g / cm 3 - 1.5 g / cm 3 ; The lithium supplement additive is in particle morphology, and its particle size is 1 μm≤D50≤10 μm, D10 / D50≥0.3, D90 / D50≤2; The lithium supplement additive includes an iron-based lithium supplement additive, and the molecular formula of the iron-based lithium supplement additive is aLiFeO2·bLi2O·cM x O y , wherein a, b, and c in the molecular formula are molar numbers, and a+b≥0.98, c≤0.02; 1.8≤b / a≤2.1; M is a doping element; 1≤y / x≤2.
5.
2. The lithium supplement additive according to claim 1, characterized in that: The loose bulk density BD and the tap density TD satisfy: (TD-BD) / TD≤40%; and / or The lithium supplement additive is in the form of particles.
3. The lithium supplement additive according to claim 2, characterized in that: The lithium supplement additive is a core-shell structure, and the core body includes the aLiFeO2·bLi2O·cM x O y The iron-based lithium supplement material is further coated with a hydrophobic encapsulation layer on the surface of the core.
4. The lithium supplement additive according to claim 3, characterized in that: The doping element includes at least one of Ni, Co, Mn, Ti, Al, Cu, V, and Zr; and / or The hydrophobic encapsulation layer comprises an ion conductor encapsulation layer and / or an electronic conductor encapsulation layer, and the ion conductor encapsulation layer or the electronic conductor encapsulation layer is coated on the surface of the lithium supplementing material in particle morphology.
5. The lithium supplement additive according to any one of claims 1 to 4, characterized in that: The BET specific surface area of the lithium supplement additive is 0.5≤BET≤20m 2 / g; and / or The resistivity of the lithium supplement additive is 1.0-500 Ω / cm.
6. A method for preparing a lithium supplement additive, comprising the following steps: Provide lithium supplement additive precursors; The lithium supplement additive precursor is subjected to a first sintering treatment to generate a lithium supplement additive, and the loose bulk density BD of the lithium supplement additive is 0.45 g / cm 3 -0.85 g / cm 3 , the tap density TD is 0.8 g / cm 3 - 1.5g / cm 3 ; The lithium supplement additive is in particle morphology, and its particle size is 1 μm≤D50≤10 μm, D10 / D50≥0.3, D90 / D50≤2; The lithium supplement additive includes an iron-based lithium supplement additive, and the molecular formula of the iron-based lithium supplement additive is aLiFeO2·bLi2O·cM x O y ;in, a, b, c in the molecular formula are molar numbers, and a+b≥0.98, c≤0.02; 1.8≤b / a≤2.1; M is a doping element; 1≤y / x≤2.
5.
7. The preparation method according to claim 6, characterized in that: The preparation method of the iron-based lithium supplement additive comprises the following steps: According to the molecular formula aLiFeO2·bLi2O·cM x O y An iron source, a lithium source, and a doping element source shown in M are mixed in a stoichiometric ratio to form a precursor; The precursor is subjected to the sintering treatment to generate a LiFeO2·bLi2O·cM x O y Iron-based lithium supplement additives; and / or The temperature of the first sintering treatment is 600-1000° C. and the time is 4-48 hours; and / or The first sintering treatment is to increase the temperature to the sintering treatment temperature at a heating rate of 10-500°C / h; and / or After the first sintering step, the second sintering step is also included: The product after the first sintering treatment is crushed and classified, and then heated to 600-1000° C. at 0-500° C. / h for 1-20 hours, and then crushed and classified again.
8. The preparation method according to claim 7, characterized in that: In the step of mixing the iron source, the lithium source and the doping element source, a carbon source is also added; the total mass of the carbon source and the reactants is 5wt%-50wt%; and / or After the first sintering treatment or the second sintering treatment, the method further includes forming a hydrophobic encapsulation layer on the surface of the lithium supplementing material subjected to the first sintering treatment or the second sintering treatment; and / or The iron source comprises at least one of iron oxide, iron nitrate, iron chloride, iron hydroxide, iron oxalate and iron acetate; and / or The lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, lithium oxide, and lithium oxalate; and / or The doping element source includes at least one of Cu, Co, Al, Ti, Fe, V, and Zr sources.
9. An electrode, characterized in that: It comprises a current collector and an electrode active layer bonded to the surface of the current collector, wherein the electrode active layer comprises an electrode active material, a lithium supplement additive, a binder and a conductive agent; wherein the lithium supplement additive is the lithium supplement additive described in any one of claims 1 to 5 or the lithium supplement additive prepared by the preparation method described in any one of claims 6 to 8.
10. The electrode according to claim 9, characterized in that The electrode is a positive electrode, and the capacity decay rate of the positive electrode stored for 20 hours at an ambient humidity of 25% relative to the capacity decay rate of the positive electrode stored for 0.5 hours is not greater than 3%; and / or The capacity attenuation rate of the positive electrode stored for 20 hours under an ambient humidity of 10% relative to the capacity attenuation rate of the positive electrode stored for 0.5 hours is no more than 1%; The lithium supplement additive is a positive electrode lithium supplement additive, which is a core-shell structure and contains a hydrophobic encapsulation layer covering the core body.
11. A secondary battery comprising a positive electrode and a negative electrode, characterized in that: The positive electrode is the electrode according to any one of claims 10; and the lithium supplement additive contained in the electrode is a positive electrode lithium supplement additive; and / or The negative electrode is the electrode according to claim 10; and the lithium supplement additive contained in the electrode is a negative electrode lithium supplement additive.
Citation Information
Patent Citations
Positive electrode lithium supplement additive and preparation method and application thereof
CN115295795A